Enhanced fluorescence from semiconductor quantum dot-labelled cells excited at 280 nm. (1st April 2022) - McFarlane, Mollie; Hall, Nicholas; McConnell, Gail
Abstract: Semiconductor quantum dots (QDs) have significant advantages over more traditional fluorophores used in fluorescence microscopy including reduced photobleaching, long-term photostability and high quantum yields, but due to limitations in light sources and optics, are often excited far from their optimum excitation wavelengths in the deep-UV. Here, we present a quantitative comparison of the excitation of semiconductor QDs at a wavelength of 280 nm, compared to the longer wavelength of 365 nm, within a cellular environment. We report increased fluorescence intensity and enhanced image quality when using 280 nm excitation compared to 365 nm excitation for cell imaging across multiple datasets, with a highest average fluorescence intensity increase of 3.59-fold. We also find no significant photobleaching of QDs associated with 280 nm excitation and find that on average, ∼80% of cells can tolerate exposure to high-intensity 280 nm irradiation over a 6-hour period.